2007
DOI: 10.1094/cchem-84-5-0450
|View full text |Cite
|
Sign up to set email alerts
|

Managing Nitrogen and Sulfur Fertilization for Improved Bread Wheat Quality in Humid Environments

Abstract: A large proportion of the wheat (Triticum aestivum L.) milled and utilized by bakeries in the eastern United States is hard red winter wheat (HRWW). Potential for producing this higher value commodity in the eastern United States is dependent on availability of adapted HRWW cultivars that are competitive with soft red winter wheat (SRWW) cultivars and implementation of management systems to enhance end‐use quality. The effects of late‐season nitrogen (N) (0–45 kg of N/ha) applied at two growth stages (GS 45 an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
10
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 38 publications
4
10
0
Order By: Relevance
“…In the current study, 101 kg N ha −1 applied at Zadoks GS 30 also resulted in the highest grain N contents in all environments under the standard spring N rates. These effects are in agreement with previous studies of hard red winter wheat in Nebraska (Bhatta et al, 2017) and Virginia (Thomason et al, 2007), which reported improved end-use qualities with higher N application rates later in plant development. However, higher grain N, in the form of increased protein content, either has a negative or neutral effect on end-use quality in soft red winter wheat, which is largely dependent on protein quality and environment.…”
Section: Efficient Nitrogen Management For Wheat Productionsupporting
confidence: 92%
“…In the current study, 101 kg N ha −1 applied at Zadoks GS 30 also resulted in the highest grain N contents in all environments under the standard spring N rates. These effects are in agreement with previous studies of hard red winter wheat in Nebraska (Bhatta et al, 2017) and Virginia (Thomason et al, 2007), which reported improved end-use qualities with higher N application rates later in plant development. However, higher grain N, in the form of increased protein content, either has a negative or neutral effect on end-use quality in soft red winter wheat, which is largely dependent on protein quality and environment.…”
Section: Efficient Nitrogen Management For Wheat Productionsupporting
confidence: 92%
“…All replicated yield tests in Virginia were conducted according to small grain production and management protocols recommended by Brann et al (2000) with late season nitrogen applied to tests at Warsaw according to Thomason et al (2007). Conventional till yield plots were planted at 22 seeds per 0.304 m of row, with a harvest area of 4.2 m 2 .…”
Section: Methodsmentioning
confidence: 99%
“…All replicated yield tests in Virginia were conducted according to small grain production and management protocols recommended by Brann et al (2000) with late season nitrogen applied to tests at Warsaw, VA, according to Thomason et al (2007). Conventional till yield plots were planted at 22 seeds per 0.304 m of row with a harvest area of 4.2 m 2 .…”
Section: Methodsmentioning
confidence: 99%